2021
DOI: 10.1016/j.jpeds.2021.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Myopericarditis after messenger RNA Coronavirus Disease 2019 Vaccination in Adolescents 12 to 18 Years of Age

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 16 publications
4
67
1
1
Order By: Relevance
“…17 Previous studies have shown extensive myocardial involvement in adolescents with VAM in the absence of significant echocardiographic abnormalities. 4,8,9 However, marked variability in return to activity recommendations was noted in our study; almost one-half of the institutions indicated allowing these adolescents to return to full activity by 12 weeks. Only two-thirds of the institutions indicated considering a stress test prior to returning to full activity.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…17 Previous studies have shown extensive myocardial involvement in adolescents with VAM in the absence of significant echocardiographic abnormalities. 4,8,9 However, marked variability in return to activity recommendations was noted in our study; almost one-half of the institutions indicated allowing these adolescents to return to full activity by 12 weeks. Only two-thirds of the institutions indicated considering a stress test prior to returning to full activity.…”
Section: Discussionmentioning
confidence: 64%
“…16 Thus, the findings of this multi-institutional study are consistent with recently published VAERS data and affirm the findings of prior smaller reports and case-series which suggest excellent short-term outcomes in these patients. [4][5][6][7][8][9][10]16 In addition, because the VAERS is critically dependent on reporting by practitioners and institutions, adverse events can be missed due to a lack of reporting. Our data, gathered from a large number of institutions across the US, provides an independent affirmation of the fact that serious life-threatening adverse events are extremely rare in adolescents with VAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (88%) cases occurred after the second dose of vaccine, and chest pain (100%) was the most common presenting symptom. Patients sought medical attention a median of 2 days after administration of the Pfizer mRNA COVID-19 vaccination [53]. Interestingly, most of these cases were mild and transient.…”
Section: Myopericarditis Following Covid-19 Messenger Rna Vaccinationmentioning
confidence: 99%
“…Myopericarditis occurred after vaccination has been reported following small pox, 3 DTaP, 4 and also post-Covid-19 vaccine injection. 5 Recent review shows Covid-19 vaccine-related myocardial injury usually presents in young Caucasian males with a median age of 36 years ago, at 3–10 days post-injection with. 6 Data suggest Covid-19 vaccine-related myocarditis or pericarditis are mostly associated with mRNA and rarely following the virus vector vaccine.…”
Section: Discussionmentioning
confidence: 99%